A Computerized Information System for Pathology - Hercz, L.; Laszlo, Ch. A.; Reesal, M. R. (Methods of Information in Medicine, 1975)
This paper describes a Computerized Information System for Pathology (CISP) capable of storing, retrieving and correlating essential information in pathology reports.Reports are entered in text form using established diagnostic terms recognizable in the system’s dictionary. Although some pre-editing of the report may be necessary, the comprehensive dictionary minimizes this effort. Dictionaries provide the vocabulary for a language which enables an economic storage of essential information in a compact and easily retrievable form. Reports and dictionaries stored on disk form the system’s data base.CISP consists of a set of modules shared by a, number of specific load module programs which store reports, retrieve them, and process requests. The system was programmed in PL/I on the IBM 360/75 OS computer system. CISP is operated from terminals situated in hospitals.
Keywords: Pathology Information Systems; Pathology Reports; Information Flow; Coding of Diagnostic Statements; H—ICDA; SNOP; Medical Text Analysis; Interactive Retrieval